The Analysis Study of Association of Intestinal Microbiota and Kidney Disease: A Comprehensive Systematic Review - Setiafadi, Rachmad Alsy; Nida, Nor Anisatun; Marom, Muhammad Naufal (International Medical Journal Corp. Ltd, 2024)
Background: Disruptions in gut microbiota compositiosn (dysbiosis) in kidney diseases can lead to worsened kidney function. Dysbiosis may increase intestinal permeability and systemic inflammation, allowing bacterial toxins to enter the bloodstream and exacerbate CKD and its complications. This systematic review aims to evaluate the association of intestinal microbiota and kidney disease by analyzing available studies of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Gut microbiota alterations are closely linked to chronic kidney disease (CKD) and end-stage renal disease (ESRD), impacting inflammation and disease progression. Microbial shifts offer potential diagnostic and therapeutic insights, though further research is needed for clinical application.